Medal of honor [videorecording (DVD)] - Sherman, Roger M., 1951-; Woodard, Alfre, 1953- (PBS Home Video, 2008)
Traces the history of the Medal of Honor from its inception during the Civil War through the Iraq War. Focuses on the stories of a valiant few: Sgt. Paul Smith who died protecting his company at the Baghdad Airport; a Holocaust survivor who single-handedly defends a hill during the Korean War; a Navy SEAL, a veteran of the Vietnam War, who swam for two hours in the ocean, carrying his wounded comrades to safety; a Marine at Iwo Jima who used a flamethrower to silence seven Japanese bunkers. Includes the story of the woman who won the Medal during the Civil War and then lost it.